2015
DOI: 10.1037/ppm0000035
|View full text |Cite
|
Sign up to set email alerts
|

Violent video games and physical aggression: Evidence for a selection effect among adolescents.

Abstract: Longitudinal studies investigating the relationship of aggression and violent video games are still scarce. Most of the previous studies focused on children or younger adolescents and relied on convenience samples. This paper presents data from a 1-year longitudinal study of N = 276 video game players aged 14 to 21 drawn from a representative sample of German gamers. We tested both whether the use of violent games predicts physical aggression (i.e., the socialization hypothesis) and whether physical aggression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 75 publications
(158 reference statements)
7
65
0
1
Order By: Relevance
“…Such studies have suggested that VVG effects are miniscule and may be due to competitive aspects of the games rather than violent content [5] or are entirely negligible [6]. Others have suggested that the impact of video games on youth well-being may be dose specific, with the best outcomes for moderate users, with both non-users and addicted users demonstrating greater problems [7].…”
Section: Introductionmentioning
confidence: 96%
“…Such studies have suggested that VVG effects are miniscule and may be due to competitive aspects of the games rather than violent content [5] or are entirely negligible [6]. Others have suggested that the impact of video games on youth well-being may be dose specific, with the best outcomes for moderate users, with both non-users and addicted users demonstrating greater problems [7].…”
Section: Introductionmentioning
confidence: 96%
“…Such research has found that many of those affected by violent content have preexisting dispositions and includes individuals with antisocial personality traits, elevated levels of psychoticism, trait aggressiveness, low agreeableness or low conscientiousness, and sensation seeking (Arriaga, Esteves, Carneiro, & Monteiro, 2006;Breuer, Vogelgesang, Quandt, & Festl, 2015;Ferguson, San Miguel, Garza, & Jerabeck, 2012;Giumetti & Markey, 2007;Markey & Scherer, 2009;Sigurdsson, Gudjonsson, Bragason, Kristjansdottir, & Sigfusdottir, 2006). Other factors that can play a role include environmental and sociocultural factors (e.g., family violence, peer influences, less parental involvement) (Anderson, Gentile, & Buckley, 2007;Ferguson, et al, 2012) and individual responses to arousal (Krcmar, Farrar, Jalette, & McGloin, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The Sexist Attitudes Scale used was Breuer, Kowert, et al (); Breuer, Vogelgesang, et al () adaptation of a scale devised by Brogan and Kutner (). It consists of three items rated on a five‐point scale from “strongly disagree” to “strongly agree.” These items were: “In a group of male and female members a man should take the leadership”; “A man should be responsible for all major decisions made in the family”; “Even if both partners work, the women should be responsible for taking care of the house hold.” Internal consistency was high (Cronbach α = .92).…”
Section: Methodsmentioning
confidence: 99%
“…Recent long‐term analyses also suggest that aggressive traits are not predicted by violent game play specifically (Smith, Ferguson, & Beaver, ). Other evidence, however, suggests early aggressiveness can predict later violent game play (Breuer, Vogelgesang, Quandt, & Festl, ). Thus, trait aggression is a sound candidate for a control variable for violent content.…”
Section: Introductionmentioning
confidence: 99%